Equation: y = 6 - 2x
Fill in the x numbers in the x which is next to -2 —> y = 6 - 2(0), y = 6 -2(1), y = 6 -2(3), and etc.
A) 0 —> 6
1 —> 4
2 —> 2
3 —> 0
4 —> -2
5 —> -4
B) Put a dot on y axis on number 6, then go down by 2 because your subtracting 2
C) 6 - 2x = 3
-6 -6
-2x = -3
-2/-2 -3/-2
X = 1.5
Negative. A negative number times a positive number is equal to a negative number. X multiplied by Y is a positive.
Answer: correct.
Step-by-step explanation:
Well when she hits the water h=0 so
2t^2-t-6=0 factor
2t^2-4t+3t-6=0
2t(t-2)+3(t-2)=0
(2t+3)(t-2)=0, since t>0
t=2 seconds...
However it should be noted that h(t)=-2t^2+t+6 implies that
v(t)=dh/dt=-4t+1 and
a(t)=dv/dt=-4
Since this is a free fall equation, this would suggest that the acceleration due to gravity is -4, whether that is supposed to be -4ft/s^2 or -4m/s^2, it certainly is not on this planet! :D If it is -4ft/s^2 it could be on the Moon or if it is -4m/s^2 it could be on Mars.
<span>(y^5)^2 = y^10
This is power of a power property</span>